A giant among the giants: Arthrocereus grandiflorus (Cactaceae, Cactoideae), a new species from the Brazilian Cerrado - Gonzaga, Diego Rafael; Fernandez, Eduardo Pinheiro; Moraes, Lucas; Neto, Luiz Menini; Peixoto, Ariane Luna (Phytotaxa, 2021)
Arthrocereus grandiflorus sp. nov. is described on the basis of field surveys, macro- and micromorphological (pollen grains) data, and analysis of literature. The new species is endemic to the Brazilian Cerrado and its two subpopulations were found in the municipality of Diamantina, Minas Gerais State. Comments on its morphological affinities with related taxa, geographical distribution, phenology, habitat, conservation status, and original photographs of living specimens are provided. In terms of conservation, it was assessed according to IUCN criteria as Critically Endangered (CR).